The Effect of the Pyrethroid Pesticide Fenpropathrin on the Cardiac Performance of Zebrafish and the Potential Mechanism of Toxicity - Ferry Saputra; Yu-Heng Lai; Marri Jmelou M. Roldan; Honeymae C. Alos; Charlaine A. Aventurado; Ross D. Vasquez; Chung-Der Hsiao (Biology, 2023)
Fenpropathrin, a pyrethroid insecticide, has been widely used for many years in agricultural fields. It works by disturbing the voltage-gated sodium channel, leading to paralysis and the death of the target animal. While past studies have focused on neurodegeneration following fenpropathrin poisoning in humans, relatively few pieces of research have examined its effect on other peripheral organs. This study successfully investigated the potential toxicity of fenpropathrin on the cardiovascular system using zebrafish as an animal model. Zebrafish larvae exposed to varying doses of fenpropathrin underwent an evaluation of cardiac physiology by measuring the heart rate, stroke volume, cardiac output, and shortening fraction. The blood flow velocity and the dorsal aorta diameter were also measured to assess the impact of fenpropathrin exposure on the vascular system. Furthermore, molecular docking was performed to evaluate the pesticide binding affinity to various proteins associated with the cardiovascular system, revealing the potential mechanism of the fenpropathrin cardiotoxic effect. The findings demonstrated a significant dose-dependent increase in the heart rate stroke volume, cardiac output, shortening fraction, and ejection fraction of zebrafish larvae after 24 h of acute treatment with fenpropathrin. Additionally, zebrafish treated at a concentration of 1 ppm exhibited significantly larger blood vessels in diameter and an increased blood flow velocity compared to the control group. According to molecular docking, fenpropathrin showed a high affinity for various voltage-gated sodium channels like scn1lab, cacna1sb, and clcn3. Finally, from the results, we found that fenpropathrin caused cardiomegaly, which may have been induced by the voltage-gated sodium channel disruption. This study highlights the significant disruption of fenpropathrin in the cardiovascular system and emphasizes the need for further research on the health implications of this pesticide.